Arsenic contamination in groundwater in the Red river delta, Vietnam - a review - Hung Viet Pham; Thi Kim Trang Pham; Viet Nga Dao (Vietnam Journal of Science, Technology and Engineering, 2018)
Arsenic contamination in groundwater and its effect on human health has been a growing concern over recent decades. Some of the most severe incidents occurred in South and Southeast Asia, including the Red river delta, Vietnam. The highest concentration of arsenic found in the Red river delta was 810 µg/L, 16 times higher than the standard guidelines given by WHO for levels of arsenic concentration in groundwater (50 µg/L). However, the contamination levels were not uniform in the whole area. The arsenic levels might be affected by natural factors such as the characteristics of the aquifer, the chemical composition of groundwater and by human activities such as the exploitation of groundwater in the urban and industrial areas or irrigation in rural areas. Due to the complex mobilisation of arsenic in sediment and groundwater, questions remain about arsenic distribution, which are yet to be answered and are in need of further study.